Paris : the powers that shaped the medieval city - Gajewski, Alexandra; Gajewski, Alexandra; McNeill, John; McNeill, John (Conference transactions / The British Archaeological Association, 2023)
"Paris: The Powers that shaped the Medieval City considers the various forces - royal, monastic and secular - that shaped the art, architecture and topography of Paris between c. 1100 and c. 1500, a period in which Paris became one of the foremost metropolises in the West. The chapters, written by an international group of scholars, cover the subject from many different angles. They encompass wide-ranging case studies that address architecture, manuscript illumination and stained glass, as well as questions of liturgy, religion and social life. Topics include the early medieval churches that preceded the current cathedral church of Notre-Dame and cultural production in the Paris area in the late 12th and early 13th centuries, as well as Paris's chapels and bridges. There is new evidence for the source of the c. 1240 design for a celebrated window in the Sainte-Chapelle, an evaluation of the liturgical arrangements in the new shrine-choir of Saint-Denis, built 1140-44, and a valuable assessment of the properties held by the Cistercian order in Paris in the Middle Ages. Also investigated are relationships between manuscript illuminators in the fourteenth century and representations of Paris in manuscripts and other media up to the late 15th century. Paris: The Powers that shaped the Medieval City updates and enlarges our knowledge of this key city in the Middle Ages and is for Medieval Archaeologists and Historians"--